Targeted interventions required against genital ulcers in African countries worst affected by HIV infection - O?Farrell Nigel (The World Health Organization, 2001)
ABSTRACT: It remains unclear why there is such marked variation in the severity of the human immunodeficiency virus (HIV) epidemic between African countries. The prevalence of HIV infection has reached high levels in many parts of southern Africa but in most countries of West Africa the levels are much lower. Although there is good evidence that sexually transmitted infections (STIs) and genital ulcers in particular facilitate heterosexual transmission of HIV, there is little comparative STI data from the African countries worst affected by HIV infection. A MEDLINE search covering the period 1966 to August 2000 using the keywords ??sexually transmitted diseases??, ??genital ulcers?? and ??Africa?? was performed to identify factors that might be relevant to the spread of HIV infection in countries with the highest prevalences of the virus. In the countries worst affected by HIV infection, the proportions of men and women with STI who had genital ulcers lay in the ranges 45-68% and 13-68%, respectively. The proportions were much lower in countries of West Africa than in those of southern Africa. The African countries worst affected by HIV infection should adopt a more specialized approach to STI control than hitherto and specifically target the high incidence of genital ulceration. Locally, technical STI committees should draw up country-specific guidelines taking into account the prevalence of the various causes of genital ulceration. In these countries, national AIDS control programmes and donor agencies should develop a specific focus for decreasing the incidence of genital ulcer disease.